T Cell Therapy Targeted on HLA-A02 Restricted HIV Antigen Epitopes: An Open Label Cellular Therapy Trial Using CD8+ T Cell - Liu, Sai; Sun, Jianping; Li, Zhen; Qin, Ling; Liu, Guihai; Li, Kang; Wu, Hao; Dong, Tao; Zhang, Yonghong (Frontiers in Immunology, 2019)
Objective: To test the safety and efficacy of a T cell therapy de novo targeting HLA-A02 restricted HIV antigen epitopes. Design: This was a prospective open label clinical trial, which enrolled 28 HIV+ participants and 24 of them finished the trial. The study was publicly registered at Chinese Clinical Trial Registry, www.chictr.org.cn(ChiCTR-ICR-15005775). Method: Autologous peripheral blood mononuclear cells were co-cultured with HLA-A02 restricted HIV antigen epitopes peptides to produce cell product for this therapy. The trial was divided into five time-points with the same interval period for infusion of the cell products or monitoring parameters. Symptoms, vital signs, and blood samples were collected to analyze the safety and efficacy of this therapy. Results: Two cases of adverse effects happened during this trial in test group, which recovered without medical intervention. There was no severe adverse effect that occurred. Both symptoms and laboratory tests have no statistical significant difference between test and control group. Flowcytometry analysis showed the expression of the PD-1 and CD95 molecule on the cell surface were downregulated post-treatment in the test group. Conclusions: This autologous HIV-antigen specific effector CD8+ T cellular therapy was safe. It might have an impact on immune suppression that can provide useful reference to future cell therapy trials.